Lactose Free-Milk for Young Children with Acute Diarrhea, Western of Iraq - Wisam Z. Al-Dulaimy .; Mohammed K. Al-Sabeea .; a, Muneam A. Ayyed .; Rafi Khaleel Al-Ani . (Al-Anbar Medical Journal, 2021)
Background: Secondary lactose intolerance occurs commonly from intestinal inflammation following infection recommending avoidance of milk contains lactose. Objective: To identify the role of lactose-free milk (LFM) in the treatment of acute diarrhea in children ≤ 2 years in Al-Ramadi Maternity and Childhood Teaching Hospital in Ramadi city, Iraq. Material and methods:  A single-blind randomized controlled trial study was done on babies ≤ two years old who presented with acute diarrhea. Two hundred cases were chosen randomly, 100 of them were received LFM added to the regime of management of diarrhea (group A), and the other 100 cases were received ordinary formula milk (OFM) (group B). Babies who were breastfeeding, those with chronic or bloody diarrhea, and those who received antibiotics were excluded from this study. Data about age, gender, the response ( stopping diarrhea), and its duration within 3 days were recorded. Results: The response of stopping diarrhea after 3 days among group A was 89%, while group B was 67%. There was a highly statistically significant difference between the 2 groups (P-value = 0.001). Out of 44 babies in the age group 0-6 months in group A, there were 42 (95.4%) who respond to therapy, and it was the highest age group affected. There was a high statistically significant difference (P-value = 0.003) between the rate of response and the age group in group A. However, there was no significant difference (P-value > 0.05) between the gender and the response rate. Moreover, there was no significant difference (P-value >  0.05) between the rate of response and the age and gender of the babies in group B. There was a statistically significant difference (P-value<0.05) between group A and B concerning the mean duration of response (55.06 hours ± 11.304 in group A, and 63.58 hours ± 8.727 in group B). Conclusion: There were a high response rate and rapid response among young children with acute diarrhea after giving LFM in comparison with OFM.